A new role for social work in remote Australia: Addressing psycho-social needs of farming families identified through financial counselling. (January 2015) - Doxey, Grant; McNamara, Patricia
Farming families in rural and remote parts of the world are often marginalized from social care. This article describes a phenomenological exploration of problems presenting to financial counsellors in remote south-eastern Australia. Individual and family issues, referral processes and professional competencies have been identified, along with suggested changes to service delivery. Complex psycho-social difficulties are revealed. Financial counsellors, working in isolation, are unable to adequately address these. However, no social work service has been accessible to many consumers living in remote farming communities. Social work, within interdisciplinary partnerships, is being piloted as a result of this study.